Preparation of yogurt-flavored bases by mixed lactic acid bacteria with the addition of lipase. (September 2020) - Huang, Yan-yan; Yu, Jia-jia; Zhou, Qin-yu; Sun, Li-na; Liu, Dong-mei; Liang, Ming-hua
Abstract: Yogurt-flavored bases are widely used in food industry for enhancing flavors. In this study, yogurt-flavored bases by mixed lactic acid bacteria with or without lipase were investigated, which included Streptococcus lactis ACCC 11093 (SL) and Lactobacillus casei subsp. rhamnosus 6013 (LCR), SL and Lactobacillus acidophilus 1.1878 (LAP), and SL and Lactobacillus plantarum DMDL 9010 (LP), respectively. Compared with the combination of SL and LCR and the combination of SL and LAP, the combination of SL and LP had higher production of total amino acids, volatile acids and esters, suggesting that the combination of SL and LP was more efficient to produce yogurt-flavored bases. In addition, lipase significantly increased the production of amino acids associated with sweet and bitter flavors, and resulted in rougher milk globule surface and tighter network structure compared with fermentations without the addition of lipase. Furthermore, a total of 54 volatile compounds were detected in yogurt-flavored bases. The production of volatile compounds in fermentations with and without the addition of lipase, was mainly affected by acids and esters, respectively. Therefore, the lipase is a favorable supplement for producing yogurt-flavored bases. Highlights: Fermented yogurt-flavored bases with lactic acid bacteria can produce more kinds of volatile compounds. Addition of lipase affected amino acids, network structure and fatty acids of yogurt flavor bases. Addition of lipase increased the abundance of key volatile compounds. The lipase treatment is a good option to improve flavor of food matrix.